Being known, branching out: troupes, teams and recovery. Issue 3 (28th August 2019) - Heinemeyer, Catherine Rachel; Rowe, Nick
Abstract : Purpose: The purpose of this paper is to reach beyond existing research into the mental health benefits of arts-based or educational opportunities, to discover the particular impact on members' recovery processes of being part of a committed, long-term troupe or community – specifically focussing on specialist theatre companies. Design/methodology/approach: Following a literature review investigating the growing number of theatre troupes for mental health service users, qualitative research was conducted into one such company. In-depth qualitative interviews were conducted with six company members. Thematic analysis of interview transcripts was then cross-checked and enriched through a group interview with six other members. Findings: Two overarching themes emerged: the importance of "being known" within the company (key sub-themes included "intuitive democracy" and the "paradox of reliability"), and the ways in which individuals "branched out" from this secure basis into artistic, professional and voluntary roles, while remaining company members. Research limitations/implications: The findings from this small-scale study, while not necessarily generalisable to other long-term communities of care and learning with a "troupe" or "team" structure, would provide valuable starting points for a larger-scale investigation. Practical implications: If generalisable, institutions in the mental health and educational worlds should place more emphasis on developing and resourcing long-term models of support. Social implications: The specialist theatre company model contrasts with prevalent individualised, time-limited services for those experiencing mental ill health. Originality/value: The study provides compelling narrative evidence to amplify understanding of how "connectedness" is experienced within a troupe, and may enable individuals with mental illnesses to progress further in their recovery journey.